Balinese Customary Law Perspective on The Existence of Adopted Children - I Nyoman Budiana; I Gede Putu Agus Wistama Putra (Fakultas Hukum, Universitas Warmadewa, 2024)
This research was conducted to find out what the inheritance rights of adopted children are regarding the existence of the inheritance of their adoptive parents according to Balinese customary law and what the position of adopted children is in the adoptive parents’ family according to Balinese customary law. The method in this research is descriptive legal research. Secondary legal materials are obtained from the results of literature reviews, books, statutory regulations, archives, and other materials or sources supporting this research. The results of the discussion are: 1) the inheritance rights of adopted children over the inheritance of adoptive parents according to Balinese customary law, namely, if the adopted child has carried out the Yadnya ceremony with meperas, the adopted child has the same position as the biological child and the adopted child has the right to inherit in his adoptive family. 2) The adopted child’s position towards the adoptive parents’ family according to Balinese customary law that the adopted child has the right to inherit as an heir like a biological child. The adopted child has no right to inherit the property inherited from his biological parents because his family relationship was severed at the time of the pemerasan ceremony.